KERAGAMAN HAYATI ALGA HIJAU DI PROVINSI GORONTALO - Tuiyo, Rully (Jurnal Entropi, 2009)
The Gorontalo province to the Northern part and South was restricted the area of the coast and sea that were big resources of fisheries nature. Some that could be developed were the cultivation of sea algae. The aim of this research was to identifity all the green algae kind that was found in the Gorontalo province. The method that was used that is the method survey explored that look and identified all the species of green algae that were found without the existence of the certain area unit or without transek of after wards was washed clean and was photographed with the digital camera.